2012
DOI: 10.1016/j.vaccine.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Design and initiation of a study to assess the direct and indirect effects of influenza vaccine given to children in rural India

Abstract: The burden of disease due to influenza is not well characterized for children in developing countries and the effectiveness of available influenza vaccines in lower resource settings has not been established. We initiated a prospective, longitudinal, phase IV, household-randomized, controlled, observer-blinded three year study (2009)(2010)(2011) in a rural community of India to measure the total and indirect household protective effects of immunizing children ages 6 months through 10 years with seasonal inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Second, the overall influenza rates reported here may have been influenced by the fact that almost one-half of the children had received influenza vaccine from November 2009 to January 2010. 8 While the 2009 seasonal vaccine did not contain pandemic virus, recent studies have shown that prior infection with influenza A (H1N1), 12,13 or immunization with seasonal live attenuated influenza vaccine, may confer some cross-protection against the A/(H1N1)pdm09 virus. 14,15 Thus, we believe that the current study likely represents a minimal estimate of IRs for pandemic influenza.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the overall influenza rates reported here may have been influenced by the fact that almost one-half of the children had received influenza vaccine from November 2009 to January 2010. 8 While the 2009 seasonal vaccine did not contain pandemic virus, recent studies have shown that prior infection with influenza A (H1N1), 12,13 or immunization with seasonal live attenuated influenza vaccine, may confer some cross-protection against the A/(H1N1)pdm09 virus. 14,15 Thus, we believe that the current study likely represents a minimal estimate of IRs for pandemic influenza.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that the true incidence of A(H1N1)pdm09 may even be greater than the IR we reported for the pandemic period, since the initial pandemic influenza peak was observed during August 2009 in this region but was not captured because the study reported here had not yet begun. 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the healthcare workers group, we calculated a pooled estimate of vaccine efficacy amongst 10 studies [8][9][10][11][12][13][14][15][16][17] for healthy adults aged 18-49 and results of the meta-analysis showed that pooled estimate of vaccine efficacy was equal to 66% (CI: 60-72) and there was heterogeneity between the results of the studies (Q = 13.69, P = 0.250). Regarding the school-age children, 2 studies [18,19] were included and pooled estimate of the vaccine efficacy was 64% (CI: 51-76).…”
Section: Vaccine Efficaciesmentioning
confidence: 99%